TEACHING WRITING SKILL BY USING BRAINWRITING STRATEGY - Virdyna, Nina Khayatul (OKARA: Jurnal Bahasa dan Sastra, 2016)
English is getting more crucial to be mastered since its important part in the world nowadays. It is not only as a means of communication but also a means transferring knowledge, news, and technology around the world. There are four basic skills in English such as listening, speaking, reading, and writing, every students must have problem in learning and mastering those skill. But writing is the main issue to be discussed in this article. In writing, some of the writer’s students feel difficult to determine the topic when they want to write, they are hardly to complete a writing paper because they run out of idea. In this case the students need to absorb some information to understand a word, including how to combine a word with the other words. Therefore the teacher should have a strategy to get the students understanding and overcome their problems.Teaching is about just how to encourage the learners to achieve their goals and other times it requires that we actually facilitate resources and foster experiences so students can learn, continue learning and love the process. It is an art of the teacher to know how to make the students able to create knowledge of their own. Brainstorming is one of the teaching techniques in writing that can encourage the students to think about the topic as many as possible. This technique is help the students to enrich their vocabularies then create an idea become a writing composition. By using this strategy the students will be able to improve their writing skill. Brainwriting is an alternative method to brainstorming that tries to encourage a more uniform participation within a group. Like brainstorming, it is designed to generate lots and lots of ideas in a short amount of time.